Orchitis reveals an extragonadal primary mediastinal thymic seminoma: a coincidence or not? - Athanasios Tampakis; Ekaterini Christina Tampaki; Christos Damaskos; Themistoklis Feretis; Irene Thymara; Konstantinos Kontzoglou; Periklis Tomos; Gregory Kouraklis (World Journal of Surgical Oncology, 2017)
Abstract Background Mediastinal thymic seminomas are rare male germ cell tumors with extragonadal origin that appear predominately with a cystic appearance. Case presentation A 22-year-old male was referred to our department for further investigation of a mediastinal mass discovered incidentally during routine chest X-ray. The patient has denied any symptoms including dyspnea, chest pain, cough, fever, dysphagia, hemoptysis, weight loss, and weakness. His past medical history was remarkable for orchitis, for which he had undergone a bilateral testicular biopsy, without the latter however, indicating the presence of a germ cell tumor or a premalignant lesion. Contrast-enhanced chest computed tomography revealed a lobulated and well-marginated cystic lesion in the anterior mediastinum. Differential diagnosis included mostly a multilocular thymic cyst, a lymphoma, a seminoma, or a soft tissue tumor. Resection of the mass revealed a primary thymic seminoma. Conclusions A surgical approach for the management of these tumors might be reasonable considering that an extensive sampling is mandatory to gain an appropriate biopsy preoperatively in order to securely confirm or refute the presence of a mediastinal extragonadal tumor. Orchitis might be a sign of a general disorder of the germ cells which might transform in time.